Complete remission of advanced renal cell carcinoma by chemotherapy and surgical treatment a case report - Goto, A (Hinyokika kiyo. Acta urologica Japonica, 1987)
A rare case of metastatic renal cell carcinoma which represented complete remission by chemotherapy and surgical treatment is presented. A 59-year-old female was admitted to our hospital because of general fatigue, weight loss and appetite loss. The diagnosis of right renal tumor metastasized to both lungs and extending into the inferior vena cava was made by radiographic findings. Because of very poor general condition the first choice of treatment was chemotherapy with cisdichlorodiamine platinum, adriamycin, cyclophosphamide, 1-(2-tetrahydrofuryl)-5-fluorouracil) (UFT), and OK432. Five months after the beginning of chemotherapy both lung coin lesions disappeared completely, and radical nephrectomy including venacavotomy and tumor thrombectomy was performed. At present, 6 months after the radical nephrectomy, she is free from the disease and complete remission has been obtained by oral administration of 400 mg/day UFT and 5.0 KE OK432 intracutaneous injection every week